Ateisme dalam wacana Ilmu Kalam - Wan Haslan Khairuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Atheism, which is an ideology or belief that does not acknowledge the existence of God, is increasingly becoming a discourse among Malaysian society when there are Malay individuals who openly on social media profess to leave the religion, choose to be atheists or free thinkers. In the face of life in the era of globalization or today’s borderless world, the early symptoms towards atheism such as skepticism, agnosticism, materialism, and atheism need to be given due attention in order to deal with it appropriately. This article will discuss Atheism in the discourse of Kalam (‘Ilm al-Kalam or Islamic scholastic theology). The writing of this article is based on a qualitative study with the application of content analysis methods to Islamic texts as well as primary sources in the literature of Kalam by scholars Ahl al-Sunnah wa al-Jama‘ah (Al-Asha‘irah and al-Maturidiyyah). The main issues discussed in this article are: [i] etymology, terminology and definition of atheism; [Ii] atheism in the literature of the Islamic tradition; and [iii] issues and objections to atheism. In conclusion, ‘Ilm al-Kalam is suitable for its purpose, which is to convict the Islamic faith (ithbat al-'aqa'id al-diniyyah) and reject any doubt (daf 'alshubah) is a medium such as in the face of confusion of thought whether a group that does not believe in the existence of god (atheism) ) or idolatrous groups (polytheism).